ANALISIS PEMILIHAN SUPPLIER CARDBOARD SHEETSDENGAN METODE FUZZY ANALYTICAL HIERARCHY PROCESS (F-AHP) DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION(TOPSIS) PADA PT. XYZ - Dewi Maharani (2022)
Procurement is defined as a process carried out by companies to obtain goods and services to ensure the continuity of the production and logistics processes. The selection of suppliers that has not been carried out optimally has resulted in several problems that occur in the supplier of cardboard sheets PT. XYZ, so the impact on the company's productivity decline. This study aims to determine the best alternative supplier at PT. XYZ uses the Fuzzy AHP and TOPSIS methods. Determination of criteria and sub-criteria in supplier selection is carried out using the cut off point method and obtained 5 criteria and 16 selected sub-criteria. Fuzzy AHP method is used to calculate the priority weight of each criterion and sub-criteria. Based on the results of weighting with Fuzzy AHP, quality is the main criterion in the selection of suppliers of cardboard sheets with a weight of 0.324. In the calculation of the best alternative from the six suppliers using the TOPSIS method, the highest preference value was obtained by the PDK supplier, which was 0.9014.